Perаn Female Peаcekeepers Indonesia dаlаm Misi Perdamaian United Nаtions Interim Force In Lebаnon (UNIFIL) Tаhun 2015-2017 - Ani Khairunnisa; Afa Dilla Adeliya (Universitas 17 Agustus 1945 Jakarta, 2023)
Abstract Every country certainly interacts with other countries. This interaction can take the form of cooperation (peace) or conflict. Conflicts that occur are more complex because of threats that not only come from inter-state actors but intra-state and conflicts that occur in the border regions of the country. The UN through the Peacekeeping Mission has carried out various peace operations in conflicting countries and has involved the participation of women peacekeepers based on the resolution of the UN Security Council number 1325 of 2000. One of the countries contributing to peace operations through its peacekeeping force is Indonesia. Indonesia is noted to have contributed to the peace operation through a force called the Garuda Contingent. This force was formed with the aim of being a peacekeeping force in a conflict country. Until now, Indonesia is still committed to maintaining peace by increasing active participation in peace operations, especially in conflict countries. Indonesia does not only send soldiers who are male but also women. For Indonesia, sending female peacekeepers is part of the national defense strategy. This was based on the existence of UNSC Resolution 1325 of 2000 which emphasized the important role of women in security for conflict prevention or resolution, peace building, peace keeping, rehabilitation and reconstruction. But it is unfortunate that the number of troops between women and men is still very far apart. From this it can be seen that women are considered to lack the right to be in the public sphere, especially in the field of state and defense. This view has become a patriarchal culture inherent in Indonesian society so that women are still considered marginal. Yet to support gender mainstreaming in peacekeeping missions, each contributing country should continue to strive to increase the participation of female peacekeepers in positions that reach the community.Gender Equality and Peace Keeping Operations concepts used to discuss in this paper Keywords: Female Peacekeepers, Gender Equality, UNIFIL. Abstrak Interaksi antar negara dalam hubungan internasional bisa berwujud dalam suatu Kerjasama, konflik maupun bersifat kompetisi. Kerjasama yang dilakukan antar negara juga dapat berupa upaya dalam menciptakan upaya perdamaian seperti PBB melalui Misi Pemeliharaan Perdamaian telah melakukan berbagai operasi perdamaian di negara-negara berkonflik dan telah melibatkan partisipasi pasukan perempuan (female peacekeepers) yang didasari oleh resolusi DK PBB nomor 1325 tahun 2000 yang juga merupakan strategi pertahanan negara. Salah satu negara yang berkontribusi dalam operasi perdamaian melalui pasukan perdamaiannya adalah Indonesia melalui pasukan yang Bernama Kontingen Garuda yang bertujuan sebagai pasukan perdamaian di negara konflik. Pengiriman pasukan tersebut tidak terbatas pada pengiriman tentara berjenis kelamin laki-laki tetapi juga perempuan (female peacekeepers) yang berperan dalam keamanan untuk pencegahan ataupun resolusi konflik, bina damai, penjagaan perdamaian, rehabilitasi dan rekonstruksi. Namun sayangnya bahwa jumlah pasukan antara perempuan dengan laki-laki masih sangat jauh selisihnya, hanya berjumlah 2 orang female peacekeepers Indonesia dari 850 orang jumlah pasukan karena perempuan dianggap kurang memiliki hak untuk berada di ruang publik terutama dalam bidang negara dan pertahanan. Ditambah lagi female peacekeepers Indonesia ini masih dibatasi perannya dengan adanya persyaratan bahwa tentara wanita harus memiliki tugas yang bersifat non-tempur. Hal ini dikarenakan pertempuran bukanlah sebuah kodrat dari perempuan. Sampai saat ini, jumlah perbandingan female peacekeepers Indonesia dengan laki-lakinya yakni hanya menduduki 4% untuk wanita dan 96% untuk laki-laki.Pandangan ini merupakan budaya patriarki yang melekat pada masyarakat Indonesia sehingga perempuan masih dianggap marjinal. Penulis akan menggunakan kerangka konsep Gender Equality dan Peace Keeping Operation untuk membahas masalah tersebut dalam paper ini.Kata Kunci: Penjaga Perdamaian Wanita, Kesetaraan Gender, UNIFIL.